The Investigation of NASA-POWER Reanalysis Daily Climatic Parameters for Al Madinah Al Munawarah City, Saudi Arabia - Hussain, Sajjad; Niyazi, Burhan; Elfeki, Amro; Masoud, Milad (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
Climatic parameters are the main components in meteorological and hydrological studies but their data availability in arid region like Saudi Arabia is a great problem. Remote sensing and reanalysis dataset can fill this gap and overcome this issue. The objective of this study is to evaluate the accuracy of NASA-POWER reanalysis dataset for period of three decades (1982-2012) for Al-Madinah Al-Munawarah. Maximum (Tmax), Minimum (Tmin), Average (Tavg) temperature, Relative humidity (Rh) and wind speed (Ws) were collected and compared with the observational data. The data was collected from the meteorological station of Al-Madinah Al-Munawarah Airport. The results revealed that the regression (R2) and Pearson correlation coefficient (r) were found highest (0.97, 0.98) for Tmax, while lowest (0.36, 0.60) for Ws, respectively. Minimum and average temperature performed very well presenting performance metrices (R2 and r) above 0.95. Relative humidity also nicely correlated with observed values having R2 and r, 0.76 and 0.87, respectively. The maximum percent bias (PBIAS) was found in Ws indicating an overestimation of 43.32%, while lowest (0.72%) for Tmax. Similarly, Rh presented an underestimation of about (-8.62%) while Tavg shows an overestimation of about (8.85%). However, Tmin overestimated the data by 17.18%. Mean Absolute Error (MAE) and Root Mean Squared Error (RMSE) was found highest (4.95 OC, 6.98 OC) for Rh, while Tmax found lowest (1.02 OC, 1.37 OC). The error matrix (MAE, RMSE) for Tmin remain normal (3.76 OC, 4.15 OC) and for Ws (2.61 m/s, 3.09 m/s) and Tavg (2.59 OC, 2.76 OC) it remains low. Overall, NASA-POWER dataset presented a very good relationship with observed data for all variables except Ws. However, this study indicates the potential and importance of this reanalysis dataset based on its performance that can be used for hydrological studies in Al-Madinah region.